Cuerpos tatuados, “almas” tatuadas : nuevas formas de subjetividad en la contemporaneidad (2009)
ABSTRACT: This article presents an ethnographic description of the contemporary tattooing practices from a conceptual perspective that prioritizes it’s meaning, the interactions and the lived experiences while being tattooed. This reflection attempts to reconstruct a holistic practice of tattoo that comprises the subjective world of actors as well as the related social dynamics. The main conclusions are: The emergence of a new aesthetic and lived “normalcy” at the heart of Western society and the configuration of a new subjectivity of those who are tattooed, as an interactive, innovative, emotional and reflexive process in which the body turns into a form of expression and a construction of the subject.